INDIA'S RURAL MARKET: THE FORTUNE LIES AT THE BOTTOM OF THE PYRAMID - Adsul, Ajit Damodar; Girigisavi, Balwant Dinkar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This is the literature review on the ‘Rural Market’ as it is very fascinating to all marketers in India and overseas. The review focuses on areas of marketing, nature and characteristics rural Market. It also gives importance to problems and opportunities of Rural Market. This will help to create and imbibe interest to the researchers/scholars for their further studies.